STUDI HUBUNGAN BONUS DEMOGRAFI, INDEKS PEMBANGUNAN MANUSIA, DAN INDEKS PEMBANGUNAN KETENAGAKERJAAN DENGAN PERTUMBUHAN EKONOMI - Marihot Nasution (Pusat Kajian Anggaran, 2021)
The purpose of this study was to analyze the causality between demographic bonuses, the Human Development Index (HDI), and the Employment Development Index (IPK) on regional economic growth in the territory of Indonesia. The demographic bonus has a positive effect on economic growth because the productive age population earns income, so that overall it contributes to the gross regional domestic product. HDI is a condition in which every resident is able to access development results in obtaining income, health, and education, so that it can trigger economic growth. The IPK figure is a value that describes the conditions for the success of manpower development in a composite which includes 9 (nine) very basic main indicators of manpower development and if these indicators are managed properly, it will trigger economic growth. This study uses secondary data or time series data collected from BPS and the Ministry of Manpower.